UJI AKTIVITAS ANTIDEPRESAN ISOMIRISTISIN TERHADAP IMMOBILITY TIME MENCIT PUTIH JANTAN (MUS MUSCULUS) - Sasqia Indri Maharani; Hery Muhamad Ansory; Inaratul Rizkhy Hanifah (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Isomyristicin results from myristicin isomerization and is reported to have the same biological activity as myristicin, an antidepressant. Myristicin at a specific dose causes toxicity, so it is necessary to study isomyristicin, which is estimated to have the same biological activity as myristicin. However, there has been no test related to isomyristicin having antidepressant activity. Therefore, this study aimed to determine the antidepressant activity and the optimum dose of isomyristicin to decrease the immobility time of male white mice (Mus musculus). This study used 30 male white mice divided into six groups: positive control, negative control, normal control, and isomyristicin dose 1.5 mg/Kg BW, 3 mg/Kg BW, and 6 mg/Kg BW mice. The method to measure the immobility time of male white mice is the Forced Swimming Test (FST) and Tail Suspension Test (TST) to induce depression. To analyze the normality data using a Shapiro Wilk and a one-way ANOVA to analyze the significant difference in the data. The result showed all doses of isomyristicin have the ability to antidepressant, and the optimal dose was 1,5 mg/kg BW mice with 82 % as the decrease percentage and proved by post hoc with sig. p (<0,05).